2017
DOI: 10.9734/jsrr/2017/33739
|View full text |Cite
|
Sign up to set email alerts
|

Application of Costing Techniques in Ornamental Fish Culture

Abstract: Indian fisheries resources need to be properly utilized for more foreign exchange earnings and for upgrading livelihood of ornamental fish farmers and entrepreneurs. Madurai district was purposively chosen as it is marked as an ornamental hub in South Tamil Nadu and offers a huge market for many goods and services including aquarium fishes. The primary data was collected from a random sample of 22 ornamental fish farmers using a pre-tested survey schedule during the year 2002-2003 with an objective of estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The estimate clearly indicated that major revenue loss in ornamental fish farms were due to disease incidence accompanied by environmental factors and poor water quality management. The loss (80%) due to disease incidence in fish was lower than that reported (90%) by Umamaheswari (2003).The major reason for death of fish as reported in the study could be due to lack of knowledge on scientific farming methods and the same could be evidenced by the study made by Verma (2003), where 48% of fisherwomen lack skill and knowledge on scientific practices of aquaculture in Orissa state. Water quality management is the main factor for the survival of young ones, which otherwise, poor water quality leads to disease infection of death of fish.…”
Section: Study On Annual Revenue Loss Due To Disease Incidence:-mentioning
confidence: 49%
“…The estimate clearly indicated that major revenue loss in ornamental fish farms were due to disease incidence accompanied by environmental factors and poor water quality management. The loss (80%) due to disease incidence in fish was lower than that reported (90%) by Umamaheswari (2003).The major reason for death of fish as reported in the study could be due to lack of knowledge on scientific farming methods and the same could be evidenced by the study made by Verma (2003), where 48% of fisherwomen lack skill and knowledge on scientific practices of aquaculture in Orissa state. Water quality management is the main factor for the survival of young ones, which otherwise, poor water quality leads to disease infection of death of fish.…”
Section: Study On Annual Revenue Loss Due To Disease Incidence:-mentioning
confidence: 49%
“…1. The loss (80%) due to disease incidence in fish was lower than that reported (90%) by Umamaheswari (2003). The major reason for the mortality of fish could be lack of knowledge on scientific farming methods and the same was reported by Verma (2003), who reported that 48% of fisherwomen lacked skill and knowledge on scientific practices of aquaculture in Odisha State.…”
mentioning
confidence: 69%